The acceptance of TV Islamic reality shows by the Malay community - A.Manaf, Aini Maznina; Wok, Saodah; Ismail, Rizalawati; Abdul Latif, Siti Sakinah (Universiti Sains Islam Malaysia (USIM), 2013)
Reality television has become increasingly popular since the past few years among viewers and television producers alike due to their own individual reasons. This study tries to understand the acceptance of the reality television, specifically, the genre of Islamic reality television shows among the Malay community. This is a quantitative study, which uses the survey method with questionnaire as the research instrument. The research targets at Malays from the age of 13 years old and above, nationwide. The study includes the level of TV viewing habits among the Malay community, the preference and viewing habits of Islamic reality shows, the reasons for watching and the satisfaction gained from watching the Islamic reality shows, as well as the involvement in and impact change on viewers of the programs. A total of 540 respondents were sampled and only 460 valid respondents were used for the present study. The study incorporated the uses and gratifications theory (Blumler & Katz, 1974) to understand the motives and satisfaction derived from watching Islamic reality shows. The study also tries to test the cultivation theory (Gerbner & Gross, 1976) for the viewers of the Islamic reality shows on their perception, attitude and behavior. The study found that majority of the respondents had viewed Islamic reality shows; with Imam Muda as the most popular Islamic reality show. They believed that the program is good and educational in nature. The main reason for watching it is the Islamic nature and the positive learning experience gained. The respondents also stated that watching Islamic reality shows improved their Islamic Knowledge and practices. The study found that there is a positive relationship between reasons for watching and satisfaction with watching Islamic reality shows and this supported the uses and gratification theory understudy. In addition, the study also found that there are positive relationships between perception, attitude, involvement and impact change with the extent of viewing habits to the Islamic reality shows. Thus, the cultivation theory holds true for this study. Based on the findings, it is suggested that relevant authorities take appropriate strategies to ensure that TV Islamic reality shows remain relevant, fun and up-to-date with current issues for the viewers to gain new knowledge and to reinforce that their existing Islamic knowledge and practices.